PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING DAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATA PELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Khairunnisa; Dayu Rika Perdana; Handoko; Muhammad Nurwahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was the low creative thinking ability of fourth-grade students at SD Negeri 5 Metro Pusat, which is influenced by the implementation of learning models that are not optimal, particularly Project-Based Learning and Problem-Based Learning. This study aims to investigate the impact of implementing these two learning models on students’ creative thinking abilities in the subject of Pancasila Education. The method used was a quasi-experimental design with a non-equivalent control group design. The sampling technique uses purposive sampling. Data analysis was conducted using simple linear regression tests and mean difference tests. The results of the study indicate that the implementation of Project-Based Learning and Problem-Based Learning has a significant influence on students’ creative thinking abilities. Additionally, there was a significant difference in the students' creative thinking abilities between the experimental class and the control class. Thus, it can be concluded that the implementation of Project-Based Learning and Problem-Based Learning models has a significant influence on the creative thinking abilities of fourth-grade students at SD Negeri 5 Metro Pusat.